Public Expenditure on Physical Activities and Sports on Economic Growth in Cameroon (Global Journal of Human-Social Science, 2022)
The objective of this work is to evaluate the effect of public expenditure on physical activities and sports on economic growth in Cameroon for the period 1990 to 2019 To do this we drew on theories on productive public expenditure BARRO 1990 In order to achieve this objective we used the modified version of the model based on econometric analysis from the framework inspired by the work of Romer Mankiw and Weil 1992 and which was taken up by Serge A Ayekoe 2004 to model the relationship between public spending on sport and growth We used the unit root test to check the stationarity of the variables then for robustness the Breusch-Godfrey test for autocorrelation of errors the Breush-Pagan- Godfrey BPG test for homoscedasticity the Jarque Berra normality test and the Ramsey global goodness test for model specification Then the Toda-Yamamoto causality test was carried out after which the ARDL model was estimated to assess the long and short term relationships and finally the Pesaran et al 2001 cointegration test The results of the estimates of the effect of public spending on PSA on economic growth in Cameroon show that public spending on PSA has a positive and indirect impact on economic growth in Cameroon An increase in public spending on sports of 1 of GDP accelerates growth by 0 01 in CT and 0 037 in LT The study shows that public expenditure on SPA has a role to play in economic development in Cameroon
Keywords: public expenditure; physical and sport activities; economic growth